School Closure Decisions in Alberta and Ontario during COVID-19: Discourse and Data. Issue 3 (September 2022) - Boothe, Katherine; Fiorillo, Nicole; Just, Danielle; Alvarez, Elizabeth; Davidson, Adrienne
Abstract: The COVID-19 pandemic has led to significant disruptions in Canada's public school system as provincial and territorial governments have enacted sudden and prolonged school closures. We compare the different school closure decisions in Alberta and Ontario during spring 2021, using official public briefings and publicly available data about rates of COVID-19 cases. We ask if provincial policy decisions can be explained by different epidemiological contexts and risks. We find that key epidemiological indicators such as the rate of cases were not directly linked to school closure decisions. This is important for policy makers and experts: it problematizes the assumption of a straight line between evidence and decisions and has implications for transparency and public trust in pandemic policy choices. A systematic description of the gap between evidence and policy is an important starting point for asking, What does drive decisions to close schools?